A FORMAÇÃO CONTINUADA DE PROFESSORES DE GEOGRAFIA DE FRANCISCO BELTRÃO: ANÁLISE DO PERÍODO 1995 A 2002. - Zanella, Ivo (2007)
This dissertation has as objective historically to analyze the continued formation of professors of Geography in the paranaense Southwest, Regional Nucleus of Education of Francisco Beltrão-PR. It has been broken of the initial formation. As methodological resource, if it adopts the half-structuralized interview, with opened questions, made the ten professors of Geography of this Regional Nucleus of Education, chosen teams from criterion previously established. To follow, leaving of a diagnosis of the situations of initial formation and continued formation, on the basis of the depositions of professors, detect possible deficiencies or ruptures between both and look for to raise action proposals. The one thematic has relevance for considering the singular teaching performance, and because the continued formation of Geography’s professor is placed as process of strategical importance, because of its challenges to the public school and because it refuses to become occulted before the gaps of the initial formation. The continued formation, on to practical the pedagogical one, also assumes the reflexive dimension, that is, takes the work educative, while collective work and of the professors, as individually thematic of reflection with meaning. In the workmanship of the professor Milton Santos, in its ideas of formation and humanization of the space while social activity; also in Candau, among others, how much to the formation. In this perspective and function of the used methodology - qualitative, of interpretative approach - the research field was defined: as the professor of Geography effected its initial formation; ashe effects the formation continued in the southwest scope of the Paraná; and which the public politics of teaching valuation taken the effect for the agencies of the State. It could be perceived that it had deficiencies in the quality of the initial formation; deficiency in the politics of the State for continued formation and in the initiatives of the professors was also uncovered in the same felt; e was transparent the lack of a relationship opened between the official agencies and the professors, with valuation and confidence, factors these that can intervene in positive way with the process of continuous formation. It was perceived, with significant clarity, the motivation of the professor to search the elements formers, as not only half of perfectionism, but also as resources to get professional advantages and advances. The daily professional does not demonstrate inclusion positioning clearly, that is, of defense of the workers, of disfavored the social one and economically, of the silenced copper-coloured and the descending aboriginals of the first inhabitants southwest. However, he is given to wait resulted concrete: the participation accomplishes of the professor of Geography in the continued formation and the joint of the debate with the too much involved actors southwest of the Paraná; the same participation as singular and unleashed element of the process of social inclusion; the privilegement of critics and hand-vises efforts to better reach convenience between the some cultures. Communities, schools and State, capable to interact collectively, will have the professor as interlocutor of this mediation in sight to carry through the educative-social project.